SOCS-3 Regulates Alveolar Bone Loss in Experimental Periodontitis - Papathanasiou, E. (J Dent Res, 2016)
The host immune response plays a key role in bacteria-induced alveolar bone resorption. Endogenous control of the magnitude and duration of inflammatory signaling is considered an important determinant of the extent of periodontal pathology. Suppressor of cytokine signaling (SOCS) proteins are inhibitors of cytokine signaling pathways and may play a role in restraining periodontal inflammation. We hypothesized that SOCS-3 regulates alveolar bone loss in experimental periodontitis. Periodontal bone loss was induced in 16-wk-old myeloid-specific SOCS-3-knockout and wild-type (WT) C57Bl6-B.129 mice by oral inoculation 9 times with 10(9) colony-forming units of Porphyromonas gingivalis A7436 through an oral gavage model for periodontitis. Sham controls for both types of mice received vehicle without bacteria. The mice were euthanized 6 wk after the last oral inoculation. Increased bone loss was demonstrated in P. gingivalis–infected SOCS-3-knockout mice as compared with P. gingivalis–infected WT mice by direct morphologic measurements, micro–computed tomography analyses, and quantitative histology. Loss of SOCS-3 function resulted in an increased number of alveolar bone osteoclasts and increased RANKL expression after P. gingivalis infection. SOCS-3 deficiency in myeloid cells also promotes a higher P. gingivalis lipopolysaccharide-induced inflammatory response with higher secretion of IL-1β, IL-6, and KC (IL-8) by peritoneal macrophages as compared with WT controls. Our data implicate SOCS-3 as a critical negative regulator of alveolar bone loss in periodontitis.